Negative association of composite dietary antioxidant index with risk of hepatic fibrosis in individuals underwent cholecystectomy: a cross-sectional study - Shuyao Hua; Wen Zhong; Yuanpu Sha; Mingyang Ma; Sheng Ge (Scientific Reports)
Abstract Cholecystectomy increases the incidence of metabolic associated fatty liver disease and fibrosis. Dietary antioxidants protect the liver from oxidative stress and inhibit the development of metabolic dysfunction‐associated steatotic liver disease (MASLD), yet the epidemiological evidence that links antioxidants intake to hepatic steatosis and fibrosis in patients underwent cholecystectomy is not available. Therefore, the present study aimed to investigate the association of composite dietary antioxidant index (CDAI) with the risk of hepatic steatosis and fibrosis in the cholecystectomy population. Data of 773 participants from the National Health and Nutrition Examination Survey (NHANES) 2017–2020 were analyzed. Dietary and supplementary intake of antioxidants were collected to calculate CDAI. The controlled attenuation parameter (CAP) and liver stiffness measurement (LSM) assessed by the vibration controlled transient elastography (VCTE) were used to identify hepatic steatosis and hepatic fibrosis, respectively. Weighted multivariate logistic regression and restricted cubic spline (RCS) regression were conducted to analyze the association. Weighted multivariate logistic regression analysis with full adjustment for confounding variables showed a negative association between CDAI and hepatic fibrosis in individuals underwent Scholecystectomy [OR (95%CI) = 0.87 (0.79, 0.94), P = 0.010], while non-significant association was found between CDAI and MASLD. Moreover, compared to the lowest quartile, the highest quartile of CDAI was associated with a lower risk of hepatic fibrosis [OR (95%CI) = 0.28 (0.13, 0.60), P = 0.007]. The RCS analysis further indicated a linear negative relationship between intake of CDAI, vitamin E, and selenium and the risk of hepatic fibrosis, whereas vitamin A was non-linearly negatively correlated with the risk of hepatic fibrosis (all P overall < 0.001). Our findings suggest that higher antioxidants intake, especially vitamin E, may be associated with a lower risk of hepatic fibrosis among individuals underwent cholecystectomy. Further studies are needed to validate current findings and explore the underlying mechanisms.